(untitled) (Journal of Partial Differential Equations, 2025)
The large time behaviour for a more general prey-axis system is considered. The asymptotically uniform boundedness of solutions in a suitable space is derived to ensure the dissipativity of the system. Based on the dissipativity of the system, the existence of a global attractor is obtained. The main technique used in this paper is the L^p-L^q estimation method.